(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
The world’s food needs are increasing, thereby encouraging people to look for new food sources based on biological resources. Indonesia as a tropical mega-biodiversity country has the potential for diverse food sources, including tuber-based foods, such as the taka plant (Tacca leontopetaloides (L.) Kuntze). Specifically, in Bangka Belitung Archipelago, Indonesia, this plant can be found in Membalong, Simpang Pesak, and Manggar. The problem is that this plant as a carbohydrate food source has not been used optimally by the wider community. This study was carried out qualitatively and quantitatively. Data were collected through open and free interviews with local communities, and direct field observations. Preliminary research was conducted at Herbarium Bogoriense, which investigated the morphology and distribution of the taka plant. The results of this study indicate that the people of Belitung Island use the tubers of the taka plant as the basic ingredients for making rintak cakes and crackers through traditional processes. Based on the local knowledge of the people of the Bangka and Belitung Archipelago, then proximate and mineral analysis was conducted, in which the samples were the tubers of the taka plant from those two islands. The outcome of the analysis shows that the carbohydrate content of the taka plant was 84.97-86.72%, and the starch content was 91.82%. Therefore, the use of these local tubers as an alternative to flour can be further developed to reduce dependence on wheat flour. The use of coastal land can be optimized with this plant of domestication effort.